Mother’s Perception of Anemia and Compliance of Iron Tablet Consumption during Pregnancy - Kody, Martha Meti; Landi, Melkisedek; Gunawan, Yosephina E.S.; Sukartiningsih, Maria Christina Endang; Kambuno, Norma Tiku (Open Access Macedonian Journal of Medical Sciences, 2021)
Backgound: Anemia cases are still the main problem found in pregnant women in East Nusa Tenggara Province, Indonesia, especially East Sumba Regency. Anemia is very common in pregnant women and iron deficiency is the main cause. Indonesia has a policy to provide iron supplements to pregnant women. Non-compliance of iron (Fe) tablets is one of the important challenge factors in fighting anemia. Objective: The research objective was to determine the relationship between perceptions and compliance of pregnant women on consuming iron tablets. Methods: This study involved 102 women, namely 34 pregnant women, 34 postpartum mothers and 34 breastfeeding mothers. After obtaining approval from the research ethics commission, data were collected by personal interview. Data were analyzed using the Spearman correlation statistical test. Results: A good perception of 77.5%, moderate 18.6% and less, 5.9%. It was found that the compliance of taking iron tablets was in the good category of 2.9%, sufficient 27.5% and less 69.6%. The results of the Spearman correlation test show a correlation coefficient of 0.164 and a significant 0.100 which means that there is a weak correlation and there is no relationship between perception and compliance of taking iron tablets. Conclusion: The perception of pregnant women about iron is mostly good and the compliance of pregnant women's in taking iron tablets is mostly sufficient. There was no relationship between perception and compliance of taking iron tablets in pregnant women.